Herpes zoster during arsenic trioxide therapy for acute promyelocytic leukemia. Issue 3 (23rd February 2021) - Freyer, Craig W.; Peterson, Chelsea E.; Man, Yun; Przespolewski, Amanda; Baron, Jeffrey; Luger, Selina M.
Abstract: Historically, arsenic exposure has been associated with herpes zoster (HZ) infection, however the risk is not well characterized in arsenic trioxide (ATO) treated patients with acute promyelocytic leukemia (APL). We aimed to characterize the risk of HZ in 112 ATO treated patients with APL with and without antiviral prophylaxis (AVP). HZ occurred in 13/112 (11.6%) within 6 months of completing ATO, including one case of HZ encephalitis. AVP reduced the incidence of HZ (17.5% vs. 4.1%, RR 0.24 [95% CI 0.05–1.0, p  = .025]) with a number needed to treat of 7.7. HZ despite AVP occurred later than HZ in patients without AVP (7.8 vs. 2.3 months from starting ATO, p  = .11). Older age and prior HZ increased the risk of HZ in patients not receiving AVP. Routine AVP should be considered in patients with APL receiving ATO, particularly in older patients and those with a history of HZ.